1989
DOI: 10.1007/bf02421170
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C “blank” alleles express class I gene products. Biochemical analysis of four different HLA-C “blank” polypeptides

Abstract: Monoclonal antibodies (mAbs) W6/32, HC10, and 4E were used to precipitate class I antigens from 21 selected individuals with at least one HLA-C "blank" allele. In 19 of these individuals, characteristic HLA-C banding patterns which could be precipitated by all three HLA class I mAbs were observed on one-dimensional isoelectric focusing gels--obviously the gene products of HLA-C "blank". At least four allelic HLA-C "blank" gene products with different isoelectric points could be discerned. All of them segregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…HLA-A, B, C, E, and G HC (15,16); the mAb TP25.99 (IgG1) which recognizes distinct determinants expressed on all ␤ 2 m-associated HLA-A, B, C, and E HC and on all ␤ 2 m-free HLA-A, B, C HC except A2, A10, A29, A31, 32, 33, A68.1, A69, and B73 (4,17); and the mAb L31 (9,12) which recognizes a determinant preferentially expressed on ␤ 2 m-free HLA-B HC were produced and characterized as previously described. The BALB/c mouse mAb 655 (IgG1) and its corresponding Ag, the human V␤-17 TCR-derived peptide GYSVSREKKES (p-V␤17), were used as controls.…”
Section: Cellsmentioning
confidence: 99%
“…HLA-A, B, C, E, and G HC (15,16); the mAb TP25.99 (IgG1) which recognizes distinct determinants expressed on all ␤ 2 m-associated HLA-A, B, C, and E HC and on all ␤ 2 m-free HLA-A, B, C HC except A2, A10, A29, A31, 32, 33, A68.1, A69, and B73 (4,17); and the mAb L31 (9,12) which recognizes a determinant preferentially expressed on ␤ 2 m-free HLA-B HC were produced and characterized as previously described. The BALB/c mouse mAb 655 (IgG1) and its corresponding Ag, the human V␤-17 TCR-derived peptide GYSVSREKKES (p-V␤17), were used as controls.…”
Section: Cellsmentioning
confidence: 99%
“…In most human populations, the products of 10-50% of the HLA-C alleles are not recognized by the human alloantisera used in HLA typing and are therefore defined as serologically "blank" alleles (9). However, biochemical analysis (10) and DNA cloning (11,12) demonstrate that the blank alleles are associated with functional genes and that the failure of human alloantisera to recognize HLA-C blanks is not caused by the absence of a functional HLA-C molecule at the cell surface. Snary et al (13) reported in 1977 that HLA-C molecules are expressed at the cell surface at levels much lower than either HLA-A or -B.…”
mentioning
confidence: 99%
“…Among these, only 8 are identifiable by serology, whereas 18 specificities for HLA-A locus and 28 for HLA-B locus are readily recognized by human alloantisera or monoclonal antibodies (11). Due to their weak immunogenicity and the lack .of specific reagents, >20% of HLA-C alleles are undetected and typed as "blank" in most populations (12)(13)(14); this fact has so far prevented critical evaluation of the role of HLA-Cw in transplantation.…”
mentioning
confidence: 99%